Video display unit exposure and risk of musculoskeletal symptoms during Covid-19 pandemic - Mohd Shamsul, Nurul Shazlin; Abdul Rahman, Haliza; Naim, Faridah (Human Resource Management Academic Research Society, 2022)
The number of visual display unit (VDU) users is growing dramatically. The VDU use during open and distance learning (ODL) frequently forces the users to adopt a repetitive motion, and static and sustained postures leading to an increased risk of musculokseletal symptoms (MSS). The study aimed to assess the ergonomic risk factors (ERFs) on MSS when working with VDU among undergraduate students in USM Health Campus (USMKK). A cross-sectional study was conducted among 385 undergraduate students in USMKK. A modified and adapted questionnaire was used to assess the demographic, VDU risk factors and Nordic Musculoskeletal Questionnaire. The data were analyzed using descriptive and inferential statistics; Chi-Square and Logistic Regression tests. The highest six-month prevalence of MSS was neck (75.7%). Chi-Square test revealed that the six months prevalence of MSS on body regions that have significantly associated with gender are shoulder, upper back, lower back, and knees (p<0.05). Duration of exposure to VDU screen for more than 6 hours/day for ODL increased the risk of shoulder [Odd Ratio (OR) and 95% Confidence Interval (CI): 4.34(1.71- 10.99)], upper back [OR(95% CI): 3.34(1.33-8.37)] and lower back pain [OR(95% CI): 4.19(1.68- 10.42)]. Exposure to VDU for 4-6 hours/day was also associated with shoulder and lower back pain. Chair, desk and accessories factor increased the risk of shoulder, elbow, wrists/hands, upper back, hips/thigh and knees pain. The results of this study indicated that ERFs when working with VDUs were associated with the chronic MSS. These association patterns also suggest opportunities for intervention strategies in order to stimulate an ergonomic workplace setting.